The barriers and facilitators of herpes zoster vaccination intentions of urban residents in China: a qualitative study - Beibei Yuan; Chao Long; Ming Wang; Elizabeth Maitland; Stephen Nicholas; Xianjing Qin; Weiying Zhao; Dawei Zhu; Ping He (Global Health Research and Policy)
Abstract Background In an aging society, herpes zoster (HZ) increases the health burden on infected patients. While quantitative studies point to a lack of willingness to accept the HZ vaccine in China, there is limited number of studies with in-depth qualitative analysis on HZ vaccination intention. This study undertakes a qualitive study method to identify the barriers and facilitators behind urban residents’ HZ vaccination intention in three China cities, and contributes towards some targeted vaccination promotion suggestions to China and other LMICs with similar low coverage of HZ vaccination. Methods We conducted 12 focus group discussions in three cities of China. In each discussion we recruited 3 to 6 participants aged 20 and older to catch the views on the HZ vaccine from residents with a wider age range. Participants were recruited by purposive sampling techniques. Guided by the health belief model, thematic analysis was used to group participants’ HZ vaccine attitudes and to identify the barriers and facilitators to HZ vaccination. Results The attitude of 59 participants participating in the focus group discussions showed a low-level acceptability of the HZ vaccine with only 27.1% (16/59) displaying a willingness to HZ vaccine uptake. The barriers to HZ vaccination included limited or incorrect conception on HZ prevalence, risk factors, susceptibility, symptoms, prevention and treatment methods, and the high cost of the HZ vaccine. Perceived vulnerability to HZ, fear of HZ pain and individuals' financial capacity were the strongest facilitators to HZ vaccination. In addition, it was found that advocacy of HZ vaccination by health professionals or government financial subsidies to HZ vaccination, could attenuate the above barriers to HZ vaccine uptake. Conclusions Our study revealed a series of barriers and facilitators of HZ vaccination intention. We recommend HZ education and advocacy by health workers and government health officials to address the limited HZ knowledge and HZ misconceptions, and the government (or health insurance providers) to pay or subsidize the high costs of HZ vaccination to increase the HZ vaccination rate.